2017
DOI: 10.3389/fmicb.2017.02426
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib Limits Influenza A Virus Propagation by Targeting Multiple Signaling Pathways

Abstract: Influenza A viruses (IAV) can cause severe global pandemic outbreaks. The currently licensed antiviral drugs are not very effective and prone to viral resistance. Thus, novel effective and broadly active drugs are urgently needed. We have identified the cellular Raf/MEK/ERK signaling cascade as crucial for IAV replication and suitable target for an antiviral intervention. Since this signaling cascade is aberrantly activated in many human cancers, several clinically approved inhibitors of Raf and MEK are now av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 78 publications
2
14
0
Order By: Relevance
“…Classically, antiviral agents are developed by targeting certain viral components. Viral genome is highly unstable and undergoes frequent mutations; under selection pressure of a drug, virus quickly acquires (Reeves et al, 2005(Reeves et al, , 2011 EGFR Gefitinib (Iressa) Poxvirus and HCMV (Herget et al, 2004;Langhammer et al, 2011) NGFR AG879 IAV, Sendai virus, HSV-1, MHV, and rotavirus (Kumar et al, 2011a, b) PDGFR Tyrphostin A9 (A9) IAV, Sendai virus, HSV-1, MHV, and rotavirus (Kumar et al, 2011a, b) Src family kinases TG100572 HSV-1 (Sharma et al, 2011) Raf (MAP3K) Vemurafenib IAV (Holzberg et al, 2017) MEK1/2 (MAP2K) U0126 IAV, IAB, PEDV, Astrovirus, BDV, Coronavirus, JUNV and HSV-1 (Cai et al, 2007;Colao et al, 2017;Kim and Lee, 2015;Ludwig et al, 2004;Moser and Schultz-Cherry, 2008;Planz et al, 2001;Rodriguez et al, 2014 (Borgeling et al, 2014;Chulu et al, 2010;Hirasawa et al, 2003) JNK (MAPK) AS601245 IAV (Nacken et al, 2012) SP600125 IAV and HCMV (Nacken et al, 2012;Zhang et al, 2015) MNK1 CGP57380 HSV-1, Poxvirus and HCMV (Walsh et al, 2008;Walsh and Mohr, 2004;Walsh et al, 2005) drug resistance at druggable sites. After the advent of high throughput genome sequencing and genome-wide siRNA screens, thousands of cellular factors that support virus replication have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, antiviral agents are developed by targeting certain viral components. Viral genome is highly unstable and undergoes frequent mutations; under selection pressure of a drug, virus quickly acquires (Reeves et al, 2005(Reeves et al, , 2011 EGFR Gefitinib (Iressa) Poxvirus and HCMV (Herget et al, 2004;Langhammer et al, 2011) NGFR AG879 IAV, Sendai virus, HSV-1, MHV, and rotavirus (Kumar et al, 2011a, b) PDGFR Tyrphostin A9 (A9) IAV, Sendai virus, HSV-1, MHV, and rotavirus (Kumar et al, 2011a, b) Src family kinases TG100572 HSV-1 (Sharma et al, 2011) Raf (MAP3K) Vemurafenib IAV (Holzberg et al, 2017) MEK1/2 (MAP2K) U0126 IAV, IAB, PEDV, Astrovirus, BDV, Coronavirus, JUNV and HSV-1 (Cai et al, 2007;Colao et al, 2017;Kim and Lee, 2015;Ludwig et al, 2004;Moser and Schultz-Cherry, 2008;Planz et al, 2001;Rodriguez et al, 2014 (Borgeling et al, 2014;Chulu et al, 2010;Hirasawa et al, 2003) JNK (MAPK) AS601245 IAV (Nacken et al, 2012) SP600125 IAV and HCMV (Nacken et al, 2012;Zhang et al, 2015) MNK1 CGP57380 HSV-1, Poxvirus and HCMV (Walsh et al, 2008;Walsh and Mohr, 2004;Walsh et al, 2005) drug resistance at druggable sites. After the advent of high throughput genome sequencing and genome-wide siRNA screens, thousands of cellular factors that support virus replication have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza viruses take advantage of host cellular functions to support efficient viral replication. Numerous studies have reported that cell signaling pathways are involved in the influenza virus life cycle, such as NF-κB (21), Raf/mitogen-activated protein kinase/extracellular signal-regulated kinase (22), phosphatidylinositol 3-kinase/protein kinase B (23) and p38/MAPK (24) pathways. The results of a genome-wide RNA interference screen in mammalian cells revealed that 219 of the 295 factors were identified to be required for efficient wild-type influenza virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…The B-Raf (V600E) inhibitor vemurafenib, which effectively inhibits the ERK pathway, was approved by the FDA to treat orbital Erdheim-Chester disease (ECD) [88,89]. Vemurafenib, at low micromolar levels, can inhibit IFV-A replication (1000-fold reduction) via suppression of viral translation [90]. Interestingly, vemurafenib also inhibits virus-induced apoptosis in A549 cells via the suppression of apoptosis-inducing cytokines [90].…”
Section: The Erk Pathwaymentioning
confidence: 99%
“…Vemurafenib, at low micromolar levels, can inhibit IFV-A replication (1000-fold reduction) via suppression of viral translation [90]. Interestingly, vemurafenib also inhibits virus-induced apoptosis in A549 cells via the suppression of apoptosis-inducing cytokines [90]. Other Raf inhibitors, such as dabrafenib and sorafenib, were FDA-approved to treat cancer.…”
Section: The Erk Pathwaymentioning
confidence: 99%